The Effect of Puzzles on the Cognitive Development of Children Aged 5–6 Years - Nur Isnaini Khosyati; Baik Nilawati Astini; Gunawan Gunawan (Indonesian Publication Center, 2026)
This study aims to determine the effect of educational puzzles on the cognitive development of children aged 5–6 years at As-Syafa'ah Early Childhood Education (ECE). The research was prompted by the limited use of innovative learning media, which has hindered children's cognitive growth, particularly in problem-solving, logical thinking, and symbolic reasoning. A quantitative pre-experimental approach was adopted, employing a one-group pretest-posttest design with a sample of 16 children aged 5–6 years. Data were collected through structured observation checklists and documentation, then analyzed using the Shapiro-Wilk normality test and a paired-sample t-test via IBM SPSS Statistics 30. The results showed a significant increase in the mean score from 48.68 in the pretest to 78.87 in the posttest following the puzzle intervention (t=31.086, p < .001). Consequently, the null hypothesis was rejected, indicating that educational puzzles significantly enhance the cognitive development of children aged 5–6 years at As-Syafa'ah ECE. Puzzles effectively stimulated logical thinking, problem-solving abilities, and pattern-symbol recognition, proving to be an engaging and effective pedagogical tool in early childhood education.